(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
This scientific literature review, written for a First Year Writing Seminar on the psychology of eating disorders, analyzes the characteristics, diagnosis, epidemiology, and complications of anorexia nervosa. It highlights the most substantiated research from peer-reviewed journal articles to provide recommendations for prevention and treatment, as well as necessary areas of further research. Anorexia nervosa is a dangerous, multifaceted mental disorder that disrupts numerous areas of life, including mental, emotional, and physical realms. It can significantly reduce lifespan and be fatal if left untreated. It is characterized by deliberate self-starvation to reach an excessively low weight, along with other practices like overexercising. These behaviors stem from an intense fear of gaining weight and a distorted body perception. The prevalence of anorexia has overall increased since the 1960s, particularly throughout adolescent girls in modern Western cultures due to the heightened ideal of thinness. In addition to environmental risk factors, genetics can also increase the likelihood of anorexia, such as a mother with a history of eating disorders. Comorbid complications often arise with anorexia, such as anxiety disorders, obsessive-compulsive disorders, and social phobia. Physical ailments also occur, including cardiovascular diseases and osteoporosis. Although some health abnormalities linked at heart disease return to normal after a full recovery from anorexia, other diseases like osteoporosis can remain for a lifetime. People diagnosed with anorexia receive either inpatient, partial, or outpatient treatment, in combination with psychotherapy. There should be a greater movement toward body positivity in the media, and stigma around mental disorders should be eliminated. For additional context, listen to the author’s reflection on the piece below.